Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1038/s41598-018-27627-3
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profiling of periodontitis-affected gingival tissue by spatial transcriptomics

Abstract: Periodontitis is a highly prevalent chronic inflammatory disease of the periodontium, leading ultimately to tooth loss. In order to characterize the gene expression of periodontitis-affected gingival tissue, we have here simultaneously quantified and localized gene expression in periodontal tissue using spatial transcriptomics, combining RNA sequencing with histological analysis. Our analyses revealed distinct clusters of gene expression, which were identified to correspond to epithelium, inflamed areas of con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(69 citation statements)
references
References 41 publications
3
54
0
Order By: Relevance
“…12 A high level of B cell and plasmacyte gene expression was also found in a study examining periodontitis-related transcriptomes in human and nonhuman primates. 13,20…”
Section: Host Transcriptomicsmentioning
confidence: 99%
“…12 A high level of B cell and plasmacyte gene expression was also found in a study examining periodontitis-related transcriptomes in human and nonhuman primates. 13,20…”
Section: Host Transcriptomicsmentioning
confidence: 99%
“…It is striking that the ER translocation GO group was the most significantly enriched set in our analysis of the 10021/H0351.2002 donor brain, AD associated microglia, and two previous studies of diseased periodontal tissue (Ludden, 2015;Lundmark et al, 2018) . It is known that cytosolic ribosome genes are strongly co-expressed (Lee et al, 2004) .…”
Section: Discussionmentioning
confidence: 66%
“…Motivated by the gingipain hypothesis that links AD to P. gingivalis infection (Dominy et al, 2019;Singhrao and Olsen, 2019) , we searched for studies linking ER translocation genes and periodontitis ( P. gingivalis is a key periodontal pathogen). We found a spatial transcriptomics study that reported higher expression of the ER translocation genes in inflamed areas of periodontitis-affected gingival connective tissue compared to non-inflamed areas (Lundmark et al, 2018) . A second study that examined peri-implant soft tissue also found that ER translocation genes are expressed at higher levels in diseased mucosa samples (Ludden, 2015) .…”
Section: Er Translocation Genes Are Associated With Periodontitismentioning
confidence: 78%
See 1 more Smart Citation
“…ST data share many limitations of single cell RNA-seq, including low coverage and high dropout rate. So far, ST studies have relied on preprocessing pipelines inspired by single cell RNA-seq studies (Ståhl et al, 2016;Asp et al, 2017;Giacomello et al, 2017;Berglund et al, 2018;Lundmark et al, 2018;Salmen et al, 2018;Thrane et al, 2018). These include normalization of gene-wise read counts in a cell/spot by the total number of reads collected from that cell/spot.…”
Section: Dear Editormentioning
confidence: 99%